Assessing the Implementation and Institutional Impact of Community Co-governance and Culture Responsive Leadership Practices in Selected Public Elementary Schools - ERICSON PACALDO; BB. BULAK BUTAL; GAY PONCE (Advanced International Journal for Research, 2026)
This study examined the level of implementation and institutional impact of community co-governance and culture-responsive leadership practices in selected public elementary schools in the Division of Bohol during the School Year 2025–2026. It aimed to determine how participatory governance and inclusive leadership practices contribute to institutional effectiveness in terms of organizational culture, stakeholder engagement, teacher performance, and student support. A descriptive-correlational research design was employed using structured questionnaires administered to ninety (90) respondents composed of school heads, teachers, and stakeholders. Data were analyzed using frequency, percentage, weighted mean, and Pearson Product-Moment Correlation Coefficient. The findings revealed that community co-governance practices were implemented at a high level, while culture-responsive leadership practices and institutional impact were rated very high across all dimensions. Strong positive relationships were found between community co-governance and culture-responsive leadership practices, between community co-governance and institutional impact, and between culture-responsive leadership and institutional impact, indicating that increased stakeholder participation and inclusive leadership are associated with improved institutional outcomes. The study concludes that the integration of community co-governance and culture-responsive leadership practices plays a significant role in enhancing school effectiveness and fostering inclusive educational environments. Based on the results, an Integrated Community Co-Governance and Culture-Responsive Leadership Framework was developed to strengthen governance practices, promote inclusive leadership, and improve institutional effectiveness in public elementary schools.